2011
DOI: 10.1007/s10753-011-9385-6
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Ameliorates Pro-inflammatory Cytokine-Induced Endoplasmic Reticulum Stress in Human Intestinal Epithelial Cells In Vitro

Abstract: Endoplasmic reticulum stress (ER stress) in intestinal epithelial cells (IECs) plays an important role in the pathogenesis and perpetuation of inflammatory bowel disease (IBD). The aim of this study is to explore the potential of berberine (BBR) in regulating pro-inflammatory cytokine-induced ER stress and apoptosis in IECs. ER stress in cultured Caco-2 cells was induced by IFN-γ/TNF-α and tunicamycin, respectively. The experimental groups were pretreated with BBR. Cell viability was determined by MTT assay. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 38 publications
(43 reference statements)
0
33
0
Order By: Relevance
“…Thus it is not surprising that IFNg and TNF-a were shown to increase ER stress in human intestinal epithelial cells in vitro. 164 It was also shown that similar to IL-10, dexamethasone enhanced MUC2 folding, reduced ER stress and up-regulated ERAD genes thereby enhancing degradation of misfolded proteins. 165 In summary, cytokines that induce ER stress in goblet cells inhibit proper mucin folding and reduce output of mucin while those that inhibit ER stress promote folding of mucins and hence enhance mucin biosynthesis and secretion to help maintain an intact and functional mucus barrier in the intestines.…”
Section: Er Stress and Mucin Regulation In Ibdmentioning
confidence: 97%
“…Thus it is not surprising that IFNg and TNF-a were shown to increase ER stress in human intestinal epithelial cells in vitro. 164 It was also shown that similar to IL-10, dexamethasone enhanced MUC2 folding, reduced ER stress and up-regulated ERAD genes thereby enhancing degradation of misfolded proteins. 165 In summary, cytokines that induce ER stress in goblet cells inhibit proper mucin folding and reduce output of mucin while those that inhibit ER stress promote folding of mucins and hence enhance mucin biosynthesis and secretion to help maintain an intact and functional mucus barrier in the intestines.…”
Section: Er Stress and Mucin Regulation In Ibdmentioning
confidence: 97%
“…[159] . Berberine has been reported to ameliorate proinflammatory cytokine-induced ERS in human intestinal epithelial cells [160] , reduce hypoxia/reoxygenation-induced human renal proximal tubular cell injury [161] , and inhibit the human immunodeficiency virus protease inhibitor-induced inflammatory response in murine macrophages [162] . Berberine has also been suggested to have an anti-hypertensive property [163] .…”
Section: Endoplasmic Reticulum Stress Is Involved In the Development mentioning
confidence: 99%
“…The most representative compounds are metformin and berberine, which exert anti-diabetic effects through activating AMPK [18,38] . Meanwhile, they are also reported to possess protective effect against ER stress [39][40][41] . Given the crucial role of ER stress in the development of pancreatic β-cell loss and insulin resistance in type 2 diabetes [6] , the alleviation of ER stress by AMPK may play an important role in treating type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%